2021
DOI: 10.1111/1744-7941.12282
|View full text |Cite
|
Sign up to set email alerts
|

The experience of work‐life balance for women doctors and nurses in Malaysia

Abstract: This paper explores how a specific context supports or hinders work-life balance (WLB) experiences focusing on women doctors and nurses in Malaysia. WLB and gender formed the conceptual basis of a qualitative study using in-depth, semi-structured interviews. The 26 participants were employed across public and private healthcare sectors. A systematic multistep data analytical procedure produced three key themes which contribute to the contemporary debate on WLB. In Malaysia, contextual factors exert a strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The demand of doctors across the world increased rapidly after the eruption of coronavirus disease 2019 . As a result, imbalance between healthcare workforce has been observed across the world (Dousin et al, 2021). Pakistan is one of those countries facing acute shortage of doctors despite being the largest skilled workforce exporter (Aman- Ullah et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…The demand of doctors across the world increased rapidly after the eruption of coronavirus disease 2019 . As a result, imbalance between healthcare workforce has been observed across the world (Dousin et al, 2021). Pakistan is one of those countries facing acute shortage of doctors despite being the largest skilled workforce exporter (Aman- Ullah et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, our research question is as follows: “does flexible working hours mediate the relationship between supervisor support to job and life satisfaction among female nurses in China?” The study offers important contribution into integrating the understanding of the issues between flexible working hours and supervisor support, where flexible working hours are an indicator of what supervisor support means; as crucial for nurses in a collectivist and patriarchal culture that emphasizes the importance of public and external roles and maintaining balance between family and professional work (Abdullah, 1996 ; Dousin, Collins, Bartram, et al., 2021 ; Dousin et al., 2021 ). Findings of the study aim not only to expand the existing nursing literature from the aspect of supervisor but also what supervisors can do to improve nurses’ job and life satisfaction, besides extending the topic which is currently understudied among nurses in China.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increase in research on work‐life balance and well‐being among nurses in recent years (see Barnett et al., 2010; Dousin, et al., 2021, Dousin, Collins, Bartram, et al. 2021; Jamieson et al., 2013; Skinner & Chapman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the level of stress associated with maintenance of a suitable work-life balance, male participants reported a higher level. In the literature, there are contradictory results, with some studies indicating that men have a better work-life balance than women, or that there is no difference [ 74 , 75 , 76 ]. Shanafelt et al demonstrated that, over time, there has been a decrease in satisfaction with work-life balance among doctors [ 77 ].…”
Section: Discussionmentioning
confidence: 99%